"Just the freedom to get good at things and stuff like that": Why spending less time at work would be good for individual, social and environmental wellbeing. (October 2022) - Balderson, Ursula; Burchell, Brendan; Kamerāde, Daiga; Coutts, Adam; Wang, Senhu
Abstract: A reduction in the average length of the working week is a policy response which is gaining increasing political and popular support for its potential help to address a number of key societal challenges, particularly the declining health and wellbeing of workers and social cohesion. Drawing on a series 40 of in-depth interviews with people who have voluntarily reduced the amount of time they spend in formal employment we use Self-Determination Theory (SDT) to show the mechanisms through which these improvements are likely to occur. SDT is a well-validated psychological theory which suggests there are three innate psychological needs which when fulfilled lead to enhanced wellbeing: relatedness, competence and autonomy. Interviews showed that when people reduced time in formal employment they dedicated more time to activities which increased the likelihood that these three psychological needs would be adequately met. The activities undertaken were also broadly compatible with a degrowth imaginary. These findings are important as they help to develop the empirical case for a transition away from an economic model focused on ever increasing economic growth and instead illustrate the potential individual, social and environmental benefits of a less work focused way of living. Highlights: When people reduced their hours of work, they spent more time doing activities beneficial for psychological wellbeing. People valued developing autonomously chosen 'competencies' rather those mandated by their work. people valued activities which promote 'relatedness'. More free time could aid the development of caring subjectivities. The popularity of flow-linked leisure activities suggests more free time may facilitate a shift away from consumerism. Increased time for autonomous activities outside work was viewed as an antidote to the alienation experienced at work.